2012
DOI: 10.1016/j.biomaterials.2012.04.041
|View full text |Cite
|
Sign up to set email alerts
|

The manipulation of natural killer cells to target tumor sites using magnetic nanoparticles

Abstract: The present work demonstrates that Cy5.5 conjugated Fe3O4/SiO2 core/shell nanoparticles could allow us to control movement of human natural killer cells (NK-92MI) by an external magnetic field. Required concentration of the nanoparticles for the cell manipulation is as low as ~20 μg Fe/mL. However, the relative ratio of the nanoparticles loaded NK-92MI cells infiltrated into the target tumor site is enhanced by 17-fold by applying magnetic field and their killing activity is still maintained as same as the NK-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 41 publications
1
77
0
2
Order By: Relevance
“…Several earlier reports have demonstrated that the in vivo movement of cells labeled with magnetic nanoparticles could be manipulated by applying a magnetic field 51–55. Our previous study have shown that MFNPs could be used for UCL/MR multimodal imaging as well as in vivo magnetically targeted cancer treatment 32.…”
Section: Resultsmentioning
confidence: 98%
“…Several earlier reports have demonstrated that the in vivo movement of cells labeled with magnetic nanoparticles could be manipulated by applying a magnetic field 51–55. Our previous study have shown that MFNPs could be used for UCL/MR multimodal imaging as well as in vivo magnetically targeted cancer treatment 32.…”
Section: Resultsmentioning
confidence: 98%
“…9,52 Moreover, these radionuclide-based methods have low anatomical resolution (PET/ SPECT) and have to be combined with other modalities such as CT (CT) or MRI, which increases the complexity of the methodology and the costs. Using optical imaging (OI), NK cells or NK cell lines (NK92) can be detected in vivo after direct ex vivo labeling with organic fluorochromes (i.e., quantum dots, Cy5.5) 23,53,54 or indirectly via transfection of a reporter gene for bioluminescence imaging (BLI) (i.e., luciferase or green fluorescent protein (GFP)). 55,56 The advantages of OI methods over MRI or PET/SPECT include cheaper cost of instrumentation, fast imaging, and radiation-free imaging.…”
mentioning
confidence: 99%
“…In this context, we used Fe 3 O 4 @SiO 2 core/shell nanoparticles to label NK cells, monitored the movement of labelled cells by MRI, and manipulated them to target tumour sites by an external magnetic field. 285 We found that the tumour-infiltrating rate of NK cells was enhanced by 17-fold through the Fe 3 O 4 @SiO 2 nanoparticle loading and magnetic field guidance, and the killing activity of NK cells was still maintained after the loading of nanoparticles. This approach could inspire future efforts to enhance the tumour-targeting efficiency of nanomedicine-carried tumour-homing cells via the external manipulation of functionalized nanomedicines.…”
Section: Battling Metastases (Secondary) Tumours By Nanomedicinesmentioning
confidence: 75%